Cerium oxide modified iridium nanorods for highly efficient electrochemical water splitting. Issue 70 (12th August 2021) - Xu, Kai; Zhu, Zizheng; Guo, Wen; Zhang, Hongyan; Yu, Tingting; Wei, Wenxian; Liang, Wenjie; Zhang, Dongen; He, Maoshuai; Yang, Tao
Abstract : Ir catalytic activities towards electrochemical oxygen evolution and hydrogen generation were greatly enhanced by Ce incorporation through interfacial electron synergism. Abstract : An Ir/CeO2 composite catalyst with Ir nanorods (NRs) on amorphous CeO2 was synthesized through a facile one-pot hydrothermal method, which shows excellent activity towards hydrogen evolution and oxygen evolution in alkaline media, even superior to the performance of commercial Pt/C, IrO2 and RuO2 catalysts. The enhanced performance could be attributed to the interfacial electron synergistic effect between Ir and CeO2 .